Multiultural Education Studies In The Perspective Of Sociology Of Education - Asep Mulyana; Rahmat Al Bayan; Midun Sopan; Feri Hardiyanto (Worldwide Research Publishing, 2023)
Indonesia is a multicultural nation with a high level of pluralism. This can be a potential for national progress as well as its decline, depending on the quality of heterogeneity management. Therefore, an understanding of the nation's motto